Extraction of antioxidant phenolic compounds by autohydrolysis of spent coffee grounds - Ballesteros, Lina F. (2014)
The extraction of antioxidant phenolic compounds from spent coffee grounds (SCG) was studied. Experimental assays were carried out by the autohydrolysis technique and the effect of the process variables temperature, water/SCG ratio and extraction time on the amount of phenolic compounds and antioxidant activity of the produced extracts was evaluated. The variables were combined according to a 23 central composite design. The statistical model revealed that the optimum condition to produce extracts with high content of phenolic compounds (35.07 mg GAE/g SCG) and antioxidant activity (FRAP = 0.25 mmol Fe(II)/g SCG, DPPH = 121.7 μmol TE/g SCG, ABTS = 130.0 μmol TE/g SCG, TAA = 64.17 mg α-TOC/g SCG) was achieved when maximizing the process variables (temperature = 200 °C, ratio = 15 ml/g and time = 50 min).